Development of knee joint angle trajectory tracking for leg support mechanism - Wan Salleh, Wan Mohd Shukri (2015)
Human assistive device is a device designed for helping human with disability and impairment problem to perform daily activities as normal person. The main categories of the assistive device are passive and active types. The active type requires power source to operate its mechanism while the passive type does not require power source. One of the important assistive devices is Knee-Ankle Foot Orthosis (KAFO) that designed for providing leg support during walking. This project is focused on the development of leg support mechanism consists of thigh and shank braces equipped with an actuator and gearing system purposely designed for providing additional support to the wearer during walking. This powered mechanism has ability of tracking the knee joint angle trajectory to imitate gait movement of a normal healthy person. The normal knee joint angle trajectory data is obtained from healthy person by using wireless Radio Frequency communication device and then plotted in Matlab Graphical User Interface (GUI) in a real-time measurement system. Proportional Integral Derivative (PID) control system is employed in this project as a controller to make sure the actuator of this mechanism moves according to the desired knee joint angle trajectory data. Designing a PID control system for knee joint angle trajectory tracking requires proper tuning of PID parameters to produce good output response. A step input is given to the system and its output response is observed while tuning these parameters. Then the actual desired knee joint angle trajectory data is given to the system and tuning process is repeated again to get best output response that shows closest angle trajectory compared to the desired trajectory.